The use of bone grafts in dental practice (Revista Nacional de Odontología, 2019)
Introduction: The aim of this study is to describe, via literature review, the use of bone grafts and the types most commonly used to rebuild following alveolar bone loss.Methodology: This literature review was conducted using the following databases: Pubmed (https://www.ncbi.nlm.nih.gov/pubmed), Scielo (http://www.scielo.org/php/index.php). The keywords for the textual search were: Bone Regeneration; Alveolar Bone Grafting; Dental Research; Dentistry. The inclusion criteria were: Literature that covers the subject under study, Literature of the last five years (from 2014 until 2019), English Language, systematic review, laboratory and clinical studies. The exclusion criteria were: literature review, letter to the editor, opinion article, literature duplicated in databases and literature that did not address the variables under study.Literature Review: 186 articles were found, but according to the inclusion criteria, only 30 were selected for this study. Bone is a specialized, vascularized and dynamic connective tissue that changes over the life of the organism. When injured, it has a unique capacity for regeneration and repair without the presence of scars, but in some situations due to the defect size, the bone tissue does not regenerate completely; thus, it is necessary to perform bone grafting procedures.Conclusion: The use of bone grafts in dentistry is shown to be a very effective and useful resource considering its great applicability in bone reconstructions in various areas of dentistry. However, greater knowledge about the viability andinfluence of biomaterials, whether associated to autogenous grafts or not, on bone repair is necessary.
Keywords: regeneración ósea; injerto de hueso alveolar; investigación dental; odontología